Between rules and resistance: moving public health emergency responses beyond fear, racism and greed. Issue 12 (5th December 2022) - Jackson, Carly; Habibi, Roojin; Forman, Lisa; Silva, Diego S.; Smith, Maxwell J.
Abstract : In times of a public health emergency, lawyers and ethicists play a key role in ensuring that government responses, such as travel restrictions, are both legally and ethically justified. However, when travel bans were imposed in a broadly discriminatory manner against southern African countries in response to the Omicron SARS-CoV-2 variant in late 2021, considerations of law, ethics or science did not appear to guide politicians' decisions. Rather, these bans appeared to be driven by fear of contagion and electoral blowback, economic motivations and inherently racist assumptions about low-income and middle-income countries (LMICs). With a new pandemic treaty and amendments to the WHO's International Health Regulations (IHR) on the near-term horizon, ethics and international law are at a key inflection point in global health governance. Drawing on examples of bordering practices to contain contagion in the current pandemic and in the distant past, we argue that the current IHR is not adequately constructed for a just and equitable international response to pandemics. Countries impose travel restrictions irrespective of their need or of the health and economic impact of such measures on LMICs. While the strengthening and reform of international laws and norms are worthy pursuits, we remain apprehensive about the transformative potential of such initiatives in the absence of collective political will, and suggest that in the interim, LMICs are justified in seeking strategic opportunities to play the same stark self-interested hardball as powerful states.